Revisiting the Curse of Natural Resources: Evidence from the Oil-Producing Countries - Royali, Ahmad Sayuti; Rosalina, Linda; Wibowo, Wisnu; Listia, Listia; Wulandari, Meisyaroh Catur (International Journal of Energy Economics and Policy, 2025)
The phenomenon of resource curse refers to the effect of the availability of a region in its natural resources. This is a special concern for oil-producing countries. The paradox of the resource curse indicates that countries with abundant natural resources are experiencing conditions of sluggish economic growth, social inequality and political instability. This study aims to analyze the dynamic relationship between oil production, the amount of oil reserves, and oil prices to GDP. The researcher analyzed in the short and long term the 4 largest oil-producing countries in the Middle East region, namely Qatar, Saudi Arabia, the United Arab Emirates, and Kuwait. Empirically, the time series data used covers the years 2013-2023 using the VECM Panel method. The results of the estimate show that there is no causal relationship, only the variable of oil reserves affects economic growth. Based on the Impulse Response Function (IRF), it shows that economic growth responds to shocks that occur on itself or two other variables, namely experiencing fluctuations at the beginning of the period and reaching equilibrium points in different periods. The results of the Variance Decomposition (VD) contribution show that oil production has a negative relationship with economic growth. The long-term results of PVECM found that oil reserves (CM) and oil production (PM) in lag 1 did not have a significant influence on economic growth. As well as the short-term results of PVECM that oil reserves (CM) have a significant influence on economic growth, while oil production (PM) does not have a significant influence in the short term. This discovery provides an interesting picture of the dynamics of natural resources, especially oil, in relation to economic growth.